Oral Ondansetron in the Prevention of Per and Post Operative Nausea and Vomiting (TAJ: Journal of Teachers Association, 2009)
A randomized single blind study was done in the Department of Anaesthesiology, Rajshahi Medical College Hospital to demonstrate the role of ondansetron, a 5-HT3 receptor antagonist, in alleviating per and post operative nausea and vomiting in patients undergoing caeserian section (CS) under subarachnoid block (SAB). For the purpose, the incidence of per and post operative nausea and vomiting were compared between matched case (n=119) and control (n=121) groups undergoing CS under SAB. Cases received 16 mg ondansetron orally one hour prior to surgery. Anti emetic prophylaxis with single dose ondansetron resulted in significant reduction of per operative and immediate post operative (2 hours) nausea and vomiting. However, at sixth post operative hour difference in nausea and vomiting between case and control groups became less significant (